Identification of the FGB gene polymorphism and analysis of its association with fat deposition traits in Hu sheep - Lijuan He; Weimin Wang; Xiaojuan Wang; Deyin Zhang; Yukun Zhang; Yuan Zhao; Liming Zhao; Xiaolong Li; Jiangbo Cheng; Dan Xu; Zongwu Ma; Xiaobin Yang; et al. (Animal Biotechnology, 2024)
As a crucial economic trait, fat deposition is directly related to carcass quality and feed efficiency in sheep. The purpose of this study was to investigate the polymorphisms of the FGB gene related to fat deposition and detect the expression features of the FGB gene in different adipose tissues of sheep by using Sanger sequencing, MassARRAY® SNP technique, and quantitative real-time PCR (qRT-PCR). Results showed that in the intron region of the FGB gene, a SNP g. 3378953 A > T has been identified, and significant association was found between perirenal fat weight, perirenal fat relative weight, mesenteric fat weight, and mesenteric fat relative weight (P < 0.05). Moreover, qRT-PCR analysis showed that FGB was expressed in all three adipose tissues, and FGB gene expression level in the AA genotype was significantly lower than that in the AT or TT genotypes (P < 0.05). Therefore, the FGB gene can be used as a candidate gene to reduce fat deposition in Hu sheep breeding, and the selection of the AA genotype in Hu sheep in production practice is more conducive to improving production efficiency.